2015
DOI: 10.1016/j.procir.2015.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Effectiveness in Sustainable Design

Abstract: Sustainable design of engineered products and systems is fantastically challenging. Think up a technology that protects the environment and perhaps a business model cannot be developed for it. Think up a business model for the technology that resonates with the market and consumers use so much of the technology that Earth would have been better without it. In the meantime the landscape is constantly shifting due to transient regulations, technology potential, and knowledge about anthropogenic impacts on Earth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…The modifications introduced in one module influences its own life cycle, but not the entire product [49]. In terms of ability to influence the product life cycle and sustainable characteristics, modularity has gained great attention in the field of sustainable design, focusing on the developing sustainable solutions, and balancing the profit of firms against environmental, economic, and social issues [11]. Newcomb et al [50] define the relationships between components as life cycle issues such as recycling, post-life intent, and service frequency and include them into a modular measure.…”
Section: Modular Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The modifications introduced in one module influences its own life cycle, but not the entire product [49]. In terms of ability to influence the product life cycle and sustainable characteristics, modularity has gained great attention in the field of sustainable design, focusing on the developing sustainable solutions, and balancing the profit of firms against environmental, economic, and social issues [11]. Newcomb et al [50] define the relationships between components as life cycle issues such as recycling, post-life intent, and service frequency and include them into a modular measure.…”
Section: Modular Designmentioning
confidence: 99%
“…Modular design is a way to life cycle assessment. In terms of the ability to influence the product life cycle and sustainable characteristics, modular design has been the focus attention in the field of sustainable design as a sustainable solution [11]. Modular design allows firms to increase their capability for production process reconfiguration and allows a more effective use of the production capacity [106].…”
Section: Modular Design and Supply Chain Flexibility And Agilitymentioning
confidence: 99%
See 1 more Smart Citation
“…impact based on its design attributes is a prohibitively challenging task [4]. Our literature review revealed that current visualization-based tools are often developed to inform designers about the sustainability-related implications of specific facets of the lifecycle.…”
Section: Introductionmentioning
confidence: 99%
“…GPs require market success to fulfill sustainable objectives [7]. Indeed, a product that shows a low environmental impact, but it is not purchased, does not contribute to sustainable development [8].…”
mentioning
confidence: 99%